2009
DOI: 10.1056/nejmoa0902604
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated with Lp(a) Lipoprotein Level and Coronary Disease

Abstract: BACKGROUND: An increased level of Lp(a) lipoprotein has been identified as a risk factor for coronary artery disease that is highly heritable. The genetic determinants of the Lp(a) lipoprotein level and their relevance for the risk of coronary disease are incompletely understood. METHODS: We used a novel gene chip containing 48,742 single-nucleotide polymorphisms (SNPs) in 2100 candidate genes to test for associations in 3145 case subjects with coronary disease and 3352 control subjects. Replication was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
980
7
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,304 publications
(1,092 citation statements)
references
References 39 publications
32
980
7
20
Order By: Relevance
“…This is in contrast to individuals of European descent, where the association of the C allele with small KIV CNV sizes and high Lp(a) concentrations was consistently demonstrated with similar numbers of variant alleles studied [21,23,28]. In East and Southeast Asians, rs3798220 C rather seems to be associated with KIV CNV sizes larger than their population mean.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This is in contrast to individuals of European descent, where the association of the C allele with small KIV CNV sizes and high Lp(a) concentrations was consistently demonstrated with similar numbers of variant alleles studied [21,23,28]. In East and Southeast Asians, rs3798220 C rather seems to be associated with KIV CNV sizes larger than their population mean.…”
Section: Discussioncontrasting
confidence: 60%
“…In these populations the variant allele of rs3798220 is associated with high Lp(a) and short KIV-2 CNV alleles, and linked to an about 70% increased risk for coronary artery disease (CAD) [21][22][23]. An allele frequency of 13% was reported in German CAD patients undergoing lipid apheresis for very high Lp(a) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Well-powered studies using this array firmly established associations between CAD and genetic variants in LPA, the gene encoding lipoprotein(a), and confirmed several early GWAS discoveries for CAD (9p21, COL4A1/COL4A2, ZC3HC1, and CYP17A1) (72,73). However, these studies also confirmed a lack of association for a vast majority of variants within candidate genes related to CAD (72,73).…”
Section: Discovery Of the First Locus Predisposing To Common Presentamentioning
confidence: 54%
“…It has been suggested that Lp(a) plays a causal role in the development of atherosclerotic diseases, and high circulating levels of Lp(a) were prospectively associated with coronary heart disease and ischemic stroke. In addition, genetically determined small isoforms of Lp(a), as a result of either kringle repeats or the above‐mentioned SNPs, were associated with cardiovascular events; that is, Mendelian randomization studies have supported a causal relationship 11, 21, 22, 23. This concept was further supported by the finding that genetically determined low levels of Lp(a) due to loss of function of the proprotein convertase subtilisin/kexin type‐9 protein were associated with reduced risks of both MI and AS 24.…”
Section: Discussionmentioning
confidence: 99%